The Threat of Aquatic Invasive Species: Understanding and Addressing Biological Pollution - Cynthia Putri Yuwana; Windri Handayani; Upi Chairun Nisa; Tety Maryenti; Ratna Yuniati; Yasman Yasman (Jurnal Ilmu Lingkungan, 2025)
This review explores the impact of aquatic invasive species as biological pollutants that disrupt ecosystems globally, including in Indonesia. Invasive species often exhibit rapid growth and reproduction due to their adaptive advantages, which, combined with human activities and favorable environmental conditions, accelerate their spread. These species alter the balance of marine and freshwater ecosystems, posing significant challenges for biodiversity conservation and resource management. Various regulatory measures have been implemented internationally, such as the European Union’s blacklist of invasive species and Indonesia’s legislative framework, to prevent their spread. Additionally, remediation techniques like zooremediation, using bivalves to mitigate biological pollutants, have been applied to manage these species. The review also highlights challenges in controlling invasive species, including the need for comprehensive ecosystem assessments and strategies like Top-Down and Bottom-Up modeling for management. Ultimately, a deeper understanding of the invasive species' ecological effects is essential for developing more effective control measures and policies, ensuring the protection of aquatic environments and mitigating the global spread of invasive species.